Afro-Science Fiction: A Study of Nnedi Okorafor’s What Sunny Saw in the Flames and Lagoon - Olaoye, Elizabeth Olubukola; Aiyetoro, Mary Bosede (Pivot: A Journal of Interdisciplinary Studies and Thought, 2016)
This paper examines the blending of Nigerian magical elements with science fiction in the writings of Nnedi Okorafor. Looking at her novels What Sunny Saw in the Flames (2011) and Lagoon (2014), we examine the juxtaposition of traditional magical elements with science fictional materials, which leads to the convergence of pseudo-realistic visions in her narratives. This paper analyses Okorafor’s novels in the context of the novelty of science fiction in Nigerian literature. Particular attention is paid to the distinctive qualities of her artistry that locates her writing within a Nigerian framework as well as within a broader global science fiction culture.